2011
DOI: 10.1289/ehp.1003283
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Asbestos and Ovarian Cancer: A Meta-analysis

Abstract: Objective: A recent Monographs Working Group of the International Agency for Research on Cancer (IARC) concluded that there is sufficient evidence for a causal association between exposure to asbestos and ovarian cancer. We performed a meta-analysis to quantitatively evaluate this association.Data sources: Searches of PubMed and unpublished data yielded a total of 18 cohort studies of women occupationally exposed to asbestos.Data extraction: Two authors independently abstracted data; any disagreement was resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 67 publications
6
59
0
8
Order By: Relevance
“…The definition of asbestiform for regulatory purposes generally sets limits on size (diameter <0.5 mm) and aspect ratio (>20:1), with additional morphological characteristics (Lowers and Meeker, 2002). It has long been known, however, that inhaling such minerals when they occur as long, thin fibers can cause disease, including those minerals that can be described as fibrous but fall outside the narrower definition of asbestiform (Agency for Toxic Substances and Disease Registry, 2001;Camargo et al, 2011;Meeker, 2009;International Agency for Research on Cancer, 2012). Naturally occurring asbestos refers to asbestos found as a natural component of rocks and soils but may include fibrous minerals that do not meet the regulatory definition of asbestos (Harper, 2008).…”
mentioning
confidence: 99%
“…The definition of asbestiform for regulatory purposes generally sets limits on size (diameter <0.5 mm) and aspect ratio (>20:1), with additional morphological characteristics (Lowers and Meeker, 2002). It has long been known, however, that inhaling such minerals when they occur as long, thin fibers can cause disease, including those minerals that can be described as fibrous but fall outside the narrower definition of asbestiform (Agency for Toxic Substances and Disease Registry, 2001;Camargo et al, 2011;Meeker, 2009;International Agency for Research on Cancer, 2012). Naturally occurring asbestos refers to asbestos found as a natural component of rocks and soils but may include fibrous minerals that do not meet the regulatory definition of asbestos (Harper, 2008).…”
mentioning
confidence: 99%
“…The animal experimental studies and the epidemiology studies all point to asbestos fibers of all types as the cause of peritoneal mesothelioma. Camargo et al [90] reviewed occupational exposure to asbestos and ovarian cancer and supported a causative association. They reiterated the diagnostic difficulty of differentiating ovarian cancer from peritoneal mesothelioma in females.…”
Section: Are Peritoneal Mesotheliomas In Women Attributable To Asbestos?mentioning
confidence: 98%
“…They reiterated the diagnostic difficulty of differentiating ovarian cancer from peritoneal mesothelioma in females. The Camargo et al [90] meta-analysis found asbestos causative for ovarian cancer. Since asbestos causes both peritoneal mesothelioma and ovarian cancer, the epidemiology picture of causation is not as difficult as the differential diagnosis between these diseases in females.…”
Section: Are Peritoneal Mesotheliomas In Women Attributable To Asbestos?mentioning
confidence: 99%
“…Trabalhadoras expostas ao asbesto e enfermeiras também mostraram um risco aumentado para câncer de ovário em alguns estudos [80][81][82] .…”
Section: Câncer De Ováriounclassified